Pelatihan Teknologi AI Menggunakan Bing Microsoft Dan Vidnoz AI Bagi Karang Taruna Kelurahan Ragunan - Sita Anggraeni; Syaifur Rahmatullah; Tyas Setiyorini; Achmad Rifai (AMMA : Jurnal Pengabdian Masyarakat, 2024)
In the Era of Society 5.0, young people have different styles of interacting, socialising, and/or absorbing knowledge. Coupled with the fact that most of today's students are from the digital generation who are accustomed to speed and convenience in other aspects of life, students expect the same speed and convenience when it comes to learning. Bing AI is an integral part of the Bing search engine platform developed by Microsoft. Built with Artificial Intelligence (AI) technology, Bing AI aims to improve users' online search experience by providing more relevant and personalised results. As video content continues to dominate the digital world, creating engaging and high-quality videos is a top priority for the younger generation in content creation. Producing videos quickly while entertaining audiences is important to stay ahead of the curve. Vidnoz is a versatile and free AI Video Generator for easy video creation, this is done through the use of Artificial Intelligence and intelligent automation. Karang Taruna Kelurahan Ragunan has many positive activities and actively spreads content on social media such as Instagram but does not yet have knowledge in the use of AI technology using Bing AI from Microsoft and the use of Vidnoz in each content. The Karang Taruna Kelurahan Ragunan administrators need insight in the form of training in the application of AI technology in the distribution of content to be shared on social media and need technical steps in the application of the use of AI technology using Bing AI from Microsoft and the use of Vidnoz. With the training in this community service, it is hoped that Karang Taruna Kelurahan Ragunan can understand the knowledge of the use of AI technology using Bing AI from Microsoft and the use of Vidnoz in every content to be shared on social media owned by Karang Taruna Kelurahan Ragunan and practice and be creative in technical steps in the application of the use of AI technology using Bing AI from Microsoft and the use of Vidnoz in every content to be shared on social media owned by Karang Taruna Kelurahan Ragunan.